Retrospective evaluation of the role of gemcitabine‐docetaxel in well‐differentiated and dedifferentiated liposarcoma. (24th September 2022) - Thirasastr, Prapassorn; Lin, Heather; Amini, Behrang; Wang, Wei‐Lien; Cloutier, Jeffrey M.; Nassif, Elise F.; Keung, Emily Z.; Roland, Christina L.; Feig, Barry; Araujo, Dejka; Benjamin, Robert S.; Conley, Anthony P.; et al.
Abstract: Objective: Well‐differentiated (WDLPS) and dedifferentiated liposarcoma (DDLPS) account for the majority of liposarcomas. Although gemcitabine‐docetaxel is used as second‐line treatment in soft tissue sarcomas, its efficacy in WDLPS/DDLPS is not established. This study retrospectively analyzed the efficacy of gemcitabine regimens in WDLPS/DDLPS. Methods: All patients with WDLPS or DDLPS who received gemcitabine‐based chemotherapy at our institution between September 2002 and January 2021 were included. Response was evaluated by an independent radiologist using RECIST 1.1. The Kaplan–Meier method was used to estimate distributions of survival outcomes and log‐rank tests were used to compare survival outcomes between subgroups. Results: Sixty‐five WDLPS/DDLPS patients were included. Seven patients (10.8%) received a gemcitabine‐based regimen more than once, totaling 72 treatments. The median age at the start of treatment was 66 years (range 32–80 years). Sixty‐five (90.3%) regimens were gemcitabine‐docetaxel, and 7 (9.7%) were gemcitabine alone. Majorities of treatments were for disease that was recurrent/metastatic (86.1%), was abdominal/retroperitoneal (83.3%), and had DDLPS components (88.9%), while 25.0% of treatments were for multifocal disease. The overall response rate was 9.7% (7/72). All responses were in patients with documented DDLPS. The median time to progression was 9.2 months (95% CI 5.3–12.3 months). The median overall survival from the start of therapy was 18.8 months (95% CI 13.1–32.4 months). Conclusion: Gemcitabine‐docetaxel is an efficacious second‐line treatment for DDLPS. Though cross study comparisons are not advisable, response to gemcitabine‐docetaxel compares favorably to current standard options trabectedin and eribulin. This combination is a valid comparator arm for future second‐line trials in DDLPS.